SELF-REPORTED URINARY INCONTINENCE DURING PREGNANCY - da Silva Souza, Lady Daiane; Lopes Barreto, Kariza (Cadernos ESP, 2023)
To identify the prevalence of self-reported urinary incontinence in pregnant women and determine the factors that influence this phenomenon. A descriptive observational epidemiological field study with a quantitative approach was conducted at a Primary Health Care Unit in the municipality of Tianguá-CE. Data collection involved a form for sociodemographic information and the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF). Following data collection, Microsoft Excel 2016 and GraphPad Prism 7.0 were used to create tables and graphs. A prevalence rate of 36.36% (n=8) of self-reported urinary incontinence during the gestational period was observed. The variables associated with this condition were cesarean delivery and a sedentary lifestyle. The findings align with existing literature and underscore the necessity for further research on this topic to enhance prevention and treatment methods.